Effect of Surface Chemical Treatment of Himalayan Nettle and Investigation of Surface, Physical and Mechanical Characteristics in Treated Nettle Fibre - R. Deepa; K. Kumaresan; K. Saravanan (Archives of Metallurgy and Materials, 2023)
The main focus of this work was the effect of chemical alkaline treatment on Himalayan nettle fibre extraction and the characterization analysis of surface-modified nettle fibre. Nettle fibre is an eco-friendly material naturally grown in the Himalayan hills of India, and it is replacing man-made fibres. The fibres are primarily bound to each other and, in turn, to the core of the plant with pectin, lignin, and gums, which begin to break down through fungal, bacterial, enzymes and chemical treatment action. The stem from the nettle plant is fibrous and has a high-quality fibre to develop nettle yarn, which is utilized to make clothes and handicrafts, mostly aimed at generating livelihood opportunities for the rural tribe’s people. This method of extraction is an effective chemical treatment for enhancing interfacial adhesion between nettle fibres and the epoxy, which is one of the significant challenges to their usage in textiles. In this paper, nettle fibres treated with chemicals such as 1% sodium hydroxide (NaOH), 0.5% sodium sulphite (Na2SO3), 0.05% ethylenediaminetetraacetic acid (EDTA), and 2% acetic acid (CH3COOH). The impact of bacterial and chemical treatments on nettle fibre and untreated nettle fibre was characterized by Fourier transform infrared spectroscopy (FTIR) analysis, which is used to study the functional elements, Scanning electron microscopy (SEM) images revealed that there is a fibre breaking mechanism and cross-section of yarn twist formation, physical and mechanical characteristics were then determined for fibre tensile strength, fibre length, Young’s modulus, elongation break, fineness, and moisture content.